Investigating Conterminous Oppositions in Khosrow, Shirin, Lily, and Majnoon of Nezami - Fatemeh Esfandiyari Mehni; Mohammad Reza Najjarian; Mohammad Khodadadi (مطالعات زبانی و بلاغی)
Conterminous opposition is a term associated with the science of syntactic semantics. The term is the accompaniment of two reciprocal elements and also it is one of the hidden arts in Nezami’s poetry. In this article, based on the theory of syntax, an attempt has been made to study and analyze its various constructions and various patterns. Of these oppositional patterns the following items have been presented: Conterminous oppositions in a sentence with the same grammatical identity, conterminous oppositions with heterogeneous grammatical identities, inflectional and non-inflectional contrast, the study of proximity magic that repeats words based on contradiction, paradox equivocality, opposition, incremental pun, dynamic pun, and also music of the conterminous oppositions. The structure of literary images using oppositions, the union of them, and their difference are intellectually very important in poetry. The association of these patterns with other rhetorical and aesthetic elements increases their semantic capacity and rhetorical beauty. This diversity has made Nezami’s poetry more dynamic in terms of rhetoric, language, and meaning. Avoiding binary opposition, which is in three forms of subversion of values, a negation of oppositions, and addition of them is one of the most important opposition in Nezami’s poetry to express the desired meaning. In this research, conterminous oppositions are introduced and syntactic structure, especially the rhetorical structure of the verses that include this art, have been analyzed aesthetically in the two poems of Khosrow and Shirin, Lily and Majnoon of Nezami.